Insect Phototaxis Mechanisms Innovations in Pest Control Strategies and Applications - Khan, Anam; Hasan, Wajid; Bisht, Kalpana; Khan, Rashid Mumtaz; Chattopadhyay, Dipanwita; Majumder, Jayeeta; Khan, Ilman; Rabeek, S. Mohamed; Ahmad, Salman (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Phototaxis, the movement of insects toward or away from light, is a critical behavioral response that influences feeding, mating, and habitat selection. Understanding the mechanisms behind insect phototaxis can lead to the development of effective and environmentally sustainable pest control strategies and explores the biological foundations of phototaxis, including the role of insect visual systems, light sensitivity, and circadian rhythms. Recent advancements in phototaxis-based pest management, particularly the use of energy-efficient LED light traps, solar-powered traps, and wavelength-specific attractants, are also discussed. These innovations offer promising alternatives to chemical pesticides, reducing environmental impact and enhancing agricultural sustainability. The integration of phototaxis-based tools with other methods, such as biological control and habitat management, is highlighted as a way to improve pest suppression while preserving beneficial insect species. Challenges, including non-target effects, variability in insect responses, and potential light pollution, are also addressed. To emphasize the need for tailored light wavelengths, smart farming integration, and eco-friendly solutions that minimize unintended ecological consequences and underscores the potential of insect phototaxis to transform pest management, offering a comprehensive framework for more sustainable agricultural practices.